UMA DOENÃ‡A BACTERIANA DA PIMENTEIRA DO REINO (Piper nigrum), NOVA PARA O BRASIL - Robbs, Charles F. (REVISTA DE AGRICULTURA, 2015)
UMA DOENÃ‡A BACTERIANA DA PIMENTEIRA DO REINO (Piper nigrum), NOVA PARA O BRASIL